Pengaruh Produktivitas Kerja dan Lingkungan Kerja terhadap Pengembangan Karir Karyawan PT Kalbe Farma Cabang Cikarang - Anggraini, Meita; Yunita, Tyna; Wahyu, Novita (Journal of Global Economic Research, 2025)
This study aims to analyze the effect of work productivity and work environment on employees' career development at PT Kalbe Farma Cikarang Branch. High work productivity and conducive work environment are important factors in increasing the career development opportunities of employees in an organization. This study used a quantitative method with Structural Equation Modeling - Partial Least Square (SEM-PLS) technique to analyze the relationship between variables. The sample in this study was 100 employees from the logistics department of PT Kalbe Farma, selected using saturated sampling technique. Data were collected by distributing questionnaires and analyzed using SmartPLS 4 software. The results showed that work productivity has a positive and significant effect on employees' career development. In addition, the work environment also contributes significantly to increasing career development opportunities. Further analysis revealed that work environment is a mediating variable between work productivity and career development. These findings confirm that organizations need to pay attention to employee productivity and create a supportive work environment to increase career development opportunities. The implications of this research provide recommendations for the management of PT Kalbe Farma in formulating more effective human resource management strategies to improve employee well-being and motivation.